Balance and Falls in Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Prospective Study. (3rd September 2017) - Oliveira, Cristino C.; Lee, Annemarie L.; McGinley, Jennifer; Anderson, Gary P.; Clark, Ross A.; Thompson, Michelle; Clarke, Sandy; Baker, Tamara; Irving, Louis B.; Denehy, Linda
ABSTRACT: Individuals with chronic obstructive pulmonary disease (COPD) have demonstrated balance impairment and a higher fall incidence. However, these have not been investigated in acute exacerbations of the disease (ECOPD). This study evaluates balance in patients during an ECOPD compared to stable COPD and healthy controls, and examines the fall incidence rate after hospitalisation due to ECOPD compared to individuals with stable COPD. Balance performance of 26 hospitalised patients with ECOPD was compared to 26 community-dwelling participants with stable COPD and 25 matched healthy controls. Balance was evaluated using computerised posturography and the Berg Balance Scale (BBS). Prospective falls were monitored by monthly calendars for 12 months in both COPD groups. Compared to controls, greater balance impairment was observed during ECOPD for most posturography variables across standing conditions ( p ≤ 0.05). Both COPD groups had worse BBS scores ( p ≤ 0.05) compared to controls. Increased dyspnoea and reduced quadriceps' strength were associated with impaired balance performance. A higher fall incidence (1.76 falls/person/year) was observed following hospitalisation in patients with ECOPD compared to stable COPD (0.53 falls/person/year) at 12 months. Patients with ECOPD demonstrate balance impairments which are associated with increased dyspnoea and reduced muscle strength. Balance impairment during ECOPD may contribute to a high incidence of falls following hospitalisation.